A preliminary assessment of genetic divergence and distribution of Malagasy cave fish in the genus Typhleotris (Teleostei: Milyeringidae) - Vences, Miguel; Rasoloariniaina, Jean R.; Riemann, Jana C. (Zootaxa, 2018)
The genus Typhleotris contains three poorly known blind fish species, inhabiting aquifers in the limestone plateau of south-western Madagascar. Until recently these species were known from only few localities, and their pattern of genetic differentiation remains poorly studied. In this study we analyse 122 Typhleotris tissue samples collected from 12 localities, spanning the entire known range of the genus, and use DNA sequences to assign these samples to the three species known. The phylogeny based on the mitochondrial marker cox1 revealed three main clades corresponding to the three species: Typhleotris madagascariensis, T. mararybe and T. pauliani, differing by uncorrected pairwise sequence divergences of 6.3-9.8%. The distribution ranges of the three species overlapped widely: T. mararybe was collected only in a southern group of localities, T. madagascariensis was found in both the southern and the central group of localities, and T. pauliani occurred from the northernmost site to the southern group of localities; yet the three species did not share haplotypes in two nuclear genes, except for three individuals that we hypothesize are hybrids of T. pauliani with T. madagascariensis and T. mararybe. This pattern of concordant mitochondrial and nuclear divergence despite sympatry strongly supports the status of all three taxa as separate species. Phylogeographic structure was obvious in T. madagascariensis, with two separate shallow mitochondrial clades occupying (1) the central vs. (2) the southern group of populations, and in T. pauliani, with separate mitochondrial clades for (1) the northern vs. (2) the central/southern populations. The widespread occurrence of these three cave fish species suggests that the aquifers in south-western Madagascar have at least in the past allowed episodic dispersal and gene flow of subterraneous organisms, whereas the phylogeographic pattern of T. madagascariensis and T. pauliani provides evidence for isolation and loss of connectivity in the more recent past.